Comparison of efficacy of diclofenac and tramadol in relieving pain in patients of acute pancreatitis: A randomized parallel group double blind active controlled pilot study. (12th December 2019) - Kumar, Nadipalli S.; Muktesh, Gaurav; Samra, Tanvir; Sarma, Phulen; Samanta, Jayanta; Sinha, Saroj K.; Dhaka, Narendra; Yadav, Thakur D.; Gupta, Vikas; Kochhar, Rakesh
Abstract: Background: Opioids and non steroidal anti inflammatory drugs (NSAIDs) are commonly used for pain relief in acute pancreatitis (AP). Opioids carry risk of sphincter of oddi constriction. Although diclofenac prevents post endoscopic retrograde cholangio‐pancreatography (ERCP) pancreatitis, few reports of diclofenac associated AP are also present. Although, both tramadol and diclofenac are commonly used for pain relief in AP, no study has evaluated their comparative efficacy and safety. Materials and Methods: Forty‐six eligible participants were randomized to either diclofenac or tramadol. Primary objectives of our study were improvement in pain intensity on visual analogue scale (VAS pain score after 1 hr of drug administration) and number of patients requiring supplementary analgesia. The secondary objectives were total number of times of supplementary analgesia requirement, time to significant decrease (33%) in VAS pain score from baseline, number of painful days (VAS pain score >5), VAS pain score on 7th day, side effects, all cause death and complications of pancreatitis between the two groups. Results: Although 46 patients were randomized, the final analysis included 41 participants. Five patients were withdrawn from the study (intubation = 3, altered sensorium = 2). No significant difference was seen in terms of VAS score after 1 hr of drug administration, number of patients requiring supplementary analgesic and number of painful days. However, time taken to significant reduction of pain was lower in the diclofenac group ( p = .028). Both the agents were comparable in terms of safety. Although complications were less in the diclofenac group, the difference was not statistically significant. Conclusion: Both diclofenac and tramadol are equally effective in controlling pain in AP with similar safety profile. Significance: There are no studies that have compared the safety and efficacy of two commonly used analgesics for pain relief in patients with AP. We found that both diclofenac and tramadol are equally effective in decreasing the pain associated with AP. There is also no significant difference in the incidence of side effects between both the groups. Hence both diclofenac and tramadol can be used safely and effectively for pain control in AP. Trial registration: The trial was registered with clinical trials registry India (Number‐ CTRI/2018/05/014309).